Chemical Composition of Essential Oils from the Heartwood of Pterocarpus macrocarpus by Different Extraction Methods in Southern China. Issue 1 (2nd January 2017) - Liu, Xiaojin; Xu, Daping; Yang, Zengjiang; Zhang, Ningnan
Abstract: Oil content and chemical composition of essential oils from heartwood of Pterocarpus macrocarpus extracted by four different extraction methods were investigated in this study. The results showed that petholeum ether extraction (PEE) got the highest oil yields in average (2.95%), followed by n-hexane extraction (NHE) (2.01%), diethyl ether extraction (DEE) (1.97%) and hydro-distillation (HD) (1.85%). A total of 71 volatile components were detected and 50 constituents were identified in the essential oil by the above four extraction methods through GC and GC-MS, most of which were alcohols, ranging from 70 to 93% of the total essential oil. The most prominent compounds were β-eudesmol, which accounting for 41-71% of the total essential oil, followed by α-eudesmol, which dominating for 8-13%, respectively. This is the first report of the essential oil composition from heartwood of P. macrocarpus planted in China.